1982
DOI: 10.2307/3898392
|View full text |Cite
|
Sign up to set email alerts
|

Cow-Calf Response to Stocking Rates, Grazing Systems, and Winter Supplementation at the Texas Experimental Ranch

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…This study confirms a well-established observation, that at least in the Great Plains, individual livestock performance tends to be as good or higher under continuous, season-long grazing than under rotation grazing (Fisher and Marion 1951, Hubbard 1951, Mcllvain and Savage 1951, Rogler 1951, Smoliak 1960, Owensby et al 1973, Currie 1978, Heitschmidt et al 1982, Heitschmidt 1986, Reece 1986, Heitschmidt and Tay1or 1991. Experiments conducted at the Central Grassland Research Center in north-central N orth Dakota for eight consecutive years have also shown similar patterns with average daily gains (ADG) for cows and calves, respectively, of 0.4 kg/d and 1.1 kg/d in the continuous, season-long grazing treatment and 0.36 kg/d and 1.09 kg/d in the twice-over rotation grazing treatment (Barker 1993).…”
Section: Aboveground C and N Flowssupporting
confidence: 88%
“…This study confirms a well-established observation, that at least in the Great Plains, individual livestock performance tends to be as good or higher under continuous, season-long grazing than under rotation grazing (Fisher and Marion 1951, Hubbard 1951, Mcllvain and Savage 1951, Rogler 1951, Smoliak 1960, Owensby et al 1973, Currie 1978, Heitschmidt et al 1982, Heitschmidt 1986, Reece 1986, Heitschmidt and Tay1or 1991. Experiments conducted at the Central Grassland Research Center in north-central N orth Dakota for eight consecutive years have also shown similar patterns with average daily gains (ADG) for cows and calves, respectively, of 0.4 kg/d and 1.1 kg/d in the continuous, season-long grazing treatment and 0.36 kg/d and 1.09 kg/d in the twice-over rotation grazing treatment (Barker 1993).…”
Section: Aboveground C and N Flowssupporting
confidence: 88%
“…Houston and Woodward (1966) ing rate on calf production cow per cow is not always this large. Heitschmidt et al (1982) found that calf production declined an average of only 7 kg cow-' as stocking rate increased from 0.132 to 0.196 head ha' and the difference between stocking rates was present in only 4 of 15 years.…”
Section: Calf Productionmentioning
confidence: 96%
“…The SDG system was stocked with growing heifers at a rate of 0.24 ha/ AU M from early April to early October. Long-term cow-calf performance data at the ranch indicate a moderate rate of stocking for mature cows under year-long continuous grazing is near 0.54 ha/ AUM (Heitschmidt et al 1982~). Rate of rotation of the heifers was such that the grazed treatment plot was grazed every 35 to 42 days for 3 to 7 days.…”
Section: Study Area and Methodsmentioning
confidence: 99%